KAJIAN STRUKTURALISME GENETIK DALAM NOVELSALAH ASUHAN KARYA ABDOEL MOEIS - Yollanda, Yollanda (Salingka, 2015)
The aim of this writing was to desribe how structuralism of Lucien Goldmann theory applied in the novel Salah Asuhan. The issue in this writing was how the theory is implemented in the novel and how to analyze the novel based on the theory. In analyzing the novel based on the theory, the writer focused on,